United Africa: realistic or not? - Bilas, Vlatka (Oeconomica Jadertina, 2020)
There is a proliferation trend of a number of regional economic integrations in the world, as well as their deepening. This global trend spilled over in Africa, where the creation and deepening of regional economic integrations with the ultimate objective/goal of establishing one continental integration is considered a development imperative. A single market of 1.3 billion people can make a difference, from the aspect of trade, productivity, competitiveness, creation of new jobs and higher living standard. This paper aims to provide an overview and discuss challenges and perspectives of the development of regional integrations in Africa with special emphasis on eight regional economic communities recognized as building blocks of the African Union. Accordingly, the contribution of the paper is twofold. First, it gives an overview of the main features of regional economic integration of Africa and the performance of eight regional economic communities. Second, it identifies the main challenges and gains of regional economic integration processes in Africa and offers recommendations for further successful regional integration processes in Africa.